N-(2-chlorobenzyl) formamide, a Novel Synthesized Antituberculosis Evaluation by Microplate Alamar Blue Assay - Desy Ayu Irma Permatasari; Ritmaleni (Proceeding of International Conference on Science, Health, And Technology, 2019)
The multicomponent amidoalkylation reaction is done by mixing three compounds simultaneously. This method develops in the area of anti-tuberculosis. Tuberculosis (TB) is an infectious disease caused by M. tuberculosis. A novel N-(2-chlorobenzyl) formamide was synthesized by reacted with formic acid or NaBH4. The synthesized compounds were identified by structural elucidation using spectroscopic methods (1H-NMR, 13C-NMR, FTIR) and GC-MS. The antituberculosis activity test used the Microplate Alamar Blue Assay (MABA) method with a concentration series of 1000-1,954 µg / mL against M. tuberculosis bacteria strain H37Rv. The results showed that the product was successfully synthesized using a multicomponent reaction with formic acid. N-(2-chlorobenzyl)formamide has MIC value 1000 μg / mL for its evaluation on antituberculosis activity with MABA method but are less potent than INH (2 μg / mL) as drug control.